Phaleria macrocarpa fruit protein aqueous extract affects viral entry, virucidal activity, and progeny release - Ismaeel, Mahmud Yusef Yusef; Chee, Wai Yip; Norefrina Shafinaz Md Nor,; Nazlina Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Presence of acyclovir (ACV) resistant virus posed a major problem in treating virus infection. Alternative treatment with the ability to encounter infection of acyclovir-resistant virus is thus needed and possibly with a different mode of action from ACV. Hence, this study evaluates the antiviral effect of Phaleria macrocarpa (Scheff.) Boerl fruit protein aqueous extract (PMFPAE) against three different strains of human herpesvirus type-1 (HHV-1) including a clinical strain, a less pathogenic strain (KOS-1), and acyclovir (ACV) resistant mutant (UKM-1). PMFPAE displayed antiviral activity towards all the HHV-1 strains when post-treated with high selective indices (SIs) of 80.6, 50, and 35, respectively. Plaque reduction percentages were reduced in attachment and penetration assays following treatment with PMFPAE indicating the ability to deactivate the early phases of the HHV-1 replication cycle. The virucidal activity was also noted following treatment of the virus with PMFPAE and this is supported by damages to the virus envelope as observed by transmission electron microscopy (TEM). Incubation of virus-treated cells with PMFPAE for 24 hr, reduced progeny release in a dose-dependent manner. The study confirms the antiviral mode of action of P. macrocarpa fruit against HHV-1 strains and the ACV-mutant strain includes inhibition during virus entry represented as the early stages of viral replication, virucidal activity, and interfering with progeny release. PMFPAE mode of action is hence different from ACV and worthy for the development of future antiviral drugs.